Festa e conflito: visões do Brasil em Oswald de Andrade - Lima, Maria Rosalete Pontes (2009)
This research intends to develop an interpretation of the images that Oswald de Andrade produced about Brazil and Brazilians in his works Pau Brazil (1925) and Marco Zero I (1943). The study began with a theoretical reflection on the relationship between modernity, nation and identity. Susbsequently, this was followed by a critique of the elements of the tradition of Brazilian thought that influenced the author and his career; in order to establish links between this thought, de Andrade’s personal background and the content of his texts. The choice of the works was guided by the history of the country and biographical details, as each work was written during different times of national significance and the author’s personal life. The first book was written during the República Velha, the zenith both artistically and financially of the author. The second was written in the Vargas era, by a Andrade now militant in the Communist Party, isolated from the elite circles with whom he used to frequent. Each piece presented its own universe of issues relating to these specific socio-historical contexts and ideological preferences of the author. It was observed that both works shared themes between the relationship with foreign countries and immigrants, the nationalist matrix and the attempts to register the idiosyncrasies of the Brazilian language. However, each evoked different versions of Brazil. A Brazil for export - of revelry, exoticisms and creative mixtures; and another Brazil - fragmented, permeated by conflicts of the most diverse origins from civil tensions demonstrated by the clash of interests of state elites, to ethnic and socio-economic struggles. Feast and conflict, celebration and war are the two axes from which the author built the Brazilian nation in his pages, and this work is an invitation for dialogue with his ideas.